Scope of education and dropout among tribal students in Kerala -A study of Scheduled tribes in Attappady - HaseenaV.A AND Ajims P. Mohammed (International Journal of Scientific and Research Publications, 2012)
Scheduled Tribes in India are generally considered to be ‘Adivasis,’ meaning indigenous people or original inhabitants of the country. The tribes have been confined to low status and are often physically and socially isolated instead of being absorbed in the mainstream Hindu population. Psychologically, the Scheduled Tribes often experience passive indifference that may take the form of exclusion from educational opportunities, social participation, and access to their own land. All tribal communities are not alike. They are products of different historical and social conditions. They belong to different racial stocks and religious backgrounds and speak different dialects. Discrimination against women, occupational differentiation, and emphasis on status and hierarchical social ordering that characterize the predominant mainstream culture are generally absent among the tribal groups. Adivasis are not as a general rule regarded as unclean or polluted in the same way as the Scheduled Caste population is perceived by the mainstream culture. However, the mainstream Hindu population considers the general tribal population as primitive, technologically backward, and illiterate. Since the 16 th century, the tribes have been perceived as sub-humans who live under primitive conditions. All the reasons are the route cause of the alienation of tribals in education and the Dropout. By giving more emphasis on other activities in the tribal hamlet, they are ignoring the value of education.